A Dynamic Equilibrium Model of Search - Michele Boldrin (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
We study a general equilibrium model where agents search for production and trading opportunities, that generalizes the existing literature by considering a large number of differentiated commodities and agents with idiosyncratic tastes. Thus, agents must chose nontrivial exchange as well as production strategies. We consider decreasing, constant, and increasing returns to scale in the matching techonoloogy, and characterize the circumstances under which there exist multiple steady state equilibria, or multiple dynamic equilibria for given initial conditions. We also characterize the existence of dynamic equilibria that are limit cycles. Equilibria are not generally optimal, and when multiple equilibria coexist they may be ranked. Pareto optimal allocations are also described and contrasted to those that obtain in equilibrium. We analyze comparative statics and find that certain intuitive results do not necessarily hold without restrictions on the stochastic structure.
Keywords: 330